Pillbox of Kedunglangkap, Kencong, Jember, East Java: A Reminder of The Japanese Colonization Era - Afandi, Mahrus; Ari Sapto; Joko Sayono (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2024)
Many evidence supports that human built structures, sites, or other relic of past activities in places deemed essential to life based on human observations of the geopolitical conditions. Topography and geographic conditions have always had an impact on human decisions to create civilizations, including pillbox construction. There is currently no study using multidisciplinary approaches to analyze the pillbox site history in Kedunglangkap, Kencong, Jember. The purpose of this study is to elucidate the aim and design of pillbox fortifications as a component of the Japanese colonial defense system, as well as the historical context related to pillbox in Kedunglangkap. In addition to the historical research methodology, this research also utilizes the archaeological investigation to explore the construction process of the pillbox in Kedunglangkap and analyze its distribution patterns. The fact that Kedunglangkap had a pillbox indicates how important the area was to the Japanese administration in the past. The pillbox site at Kedunglangkap should be preserved for the purpose of teaching history, since it is an important piece of historically relevant architecture that reminds us of the village's important role in the past.